The optimization of the Ambonese arrack fermentation using co-culture Pichia polymorpha and Kloeckera javanica - Ferymon Mahulette; Dea Indriani Astuti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mahulette F, Astuti DI. 2020. The optimization of the Ambonese arrack fermentation using co-culture Pichia Polymorpha and Kloeckera javanica. Biodiversitas 21: xxxx. The fermentation process of the Ambonese arrack is still uncontrollable. As various microbes are involved in the fermentation, which causes inconsistent production of ethanol content. This research aimed to optimize the production of the Ambonese arrack using Pichia polymorpha and Kloeckera javanica in inoculum ratios of 1:1, 1:2, and 1:3. The number of yeast cells and chemical characteristics was observed every three hrs up to 24 hrs. The ethanol content of the fermented coconut sap and the arrack was measured using the titration and Gas Chromatography-Mass Spectrophotometry (GC-MS) methods, respectively. The numbers of P. polymorpha and K. javanica cells at 15 hrs of fermentation were 9.9 log CFU/mL and 10.7 log CFU/mL, respectively. The reducing sugar content decreased from 525 mg/L to 296 mg/L, while the pH from 6.46 to 4.82. The highest ethanol production rate was 1.4 mg/L.3hrs. (ratio 1:1), observed at 12 hrs of the fermentation, while the highest ethanol contents in the fermented coconut sap and the arracks were 11.3 mg/L and 300.400 mg/L, respectively. Different inoculum ratios affect the sensory characteristics of Ambonese arrack. The highest average value of sensory testing was 4.6 (ratio 1:2). Thus, the inoculum ratios of P. polymorpha and K. javanica 1:2 and 1:3 has the best quality in controlled Ambonese arrack processing.